PEMETAAN JARING SOSIAL KE JARING SPASIAL MEMANFAATKAN TEKNIK PEMETAAN PARTISIPATIF - Nashrul Jabbaaar, Dzikri
As an acceleration of regional development in an area, a mapping method exists by positioning the community as the actor of mapping their territory, that is participatory mapping method. This method can be further developed to review neighborhood relationships in an administrative area by utilizing the latest technology. Neighborhood relationships can be formed from both social aspects (ex: population data, civil registration data, etc) and spatial aspects (spatial reference data, geotagging data, etc). However, the social data obtained has the possibility of errors when filling data so that a validation process is necessary. In this case, the integration and validation process between social and spatial data will implement the relational database concept using DBMS (Database Management System). In addition, the neighborhood relationship that is formed from spatial data will use the graph theory based on topology. In this study, the neighborhood scheme is defined so that the integration and validation process will adjust it. This study will provide a visualization of the results of integration and validation between social and spatial data using the neighborhood scheme so that spatial data can be equipped with social attributes in the form of population data.